Cancer league actions against sunbed use for skin cancer prevention. (27th February 2019) - Yared, W.; Boonen, B.; McElwee, G.; Ferguson, M.
Abstract: The incidence of non‐melanoma and melanoma skin cancer has been rising in Europe. Although the World Health Organization's International Agency for Research on Cancer has since 2009 classified sunbeds as a Group 1 carcinogen, sunbed use, especially by those under the age of 18, continues to be a concern. As the only platform for cancer leagues in Europe, the Association of European Cancer Leagues decided to explore interest and actions by its member leagues at the national level against sunbed use, to share experiences and to provide background information on possible future collective actions at the EU level.